Retromer Contributes to Immunity-Associated Cell Death in Arabidopsis. Issue 2 (13th February 2015) - Munch, David; Teh, Ooi-Kock; Malinovsky, Frederikke Gro; Liu, Qinsong; Vetukuri, Ramesh R.; El Kasmi, Farid; Brodersen, Peter; Hara-Nishimura, Ikuko; Dangl, Jeffery L.; Petersen, Morten; Mundy, John; Hofius, Daniel
Abstract : Loss of Arabidopsis retromer subunits suppresses immune receptor-mediated cell death and affects autophagy-related vacuolar processes, thus implicating retromer trafficking in cell death regulation. Abstract: Membrane trafficking is required during plant immune responses, but its contribution to the hypersensitive response (HR ), a form of programmed cell death (PCD ) associated with effector-triggered immunity, is not well understood. HR is induced by nucleotide binding-leucine-rich repeat (NB-LRR ) immune receptors and can involve vacuole-mediated processes, including autophagy. We previously isolated lazarus ( laz ) suppressors of autoimmunity-triggered PCD in the Arabidopsis thaliana mutant accelerated cell death11 ( acd11 ) and demonstrated that the cell death phenotype is due to ectopic activation of the LAZ5 NB-LRR . We report here that laz4 is mutated in one of three VACUOLAR PROTEIN SORTING35 ( VPS35 ) genes. We verify that LAZ4/VPS35B is part of the retromer complex, which functions in endosomal protein sorting and vacuolar trafficking. We show that VPS35B acts in an endosomal trafficking pathway and plays a role in LAZ5-dependent acd11 cell death. Furthermore, we find that VPS35 homologs contribute to certain forms of NB-LRR protein-mediated autoimmunity as well as pathogen-triggered HR . Finally, we demonstrate that retromer deficiency causes defects in late endocytic/lytic compartments and impairs autophagy-associated vacuolar processes. Our findings indicate important roles of retromer-mediated trafficking during the HR ; these may include endosomal sorting of immune components and targeting of vacuolar cargo.